P735Regulation of macrophage polarization by extracellular RNA: The role of sialoadhesin-1. (15th July 2014) - Cabrera-Fuentes, H A; Galuska, S; Meiler, S; Baumer, Y; Mccurdy, S; Fischer, S; Preissner, KT; Boisvert, W
Abstract: Macrophages respond to external stimuli with rapid changes in their expression of many inflammation-related genes to undergo polarization towards the M1 (pro-inflammatory) or M2 (anti-inflammatory) phenotype. This unique property of macrophages allows these cells to modulate chronic inflammatory processes such as atherogenesis. We have previously shown that extracellular RNA (eRNA) can exert prothrombotic and inflammatory properties in the vasculature as a cofactor in protease auto-activation and cytokine mobilization. Given the association of eRNA with macrophages within atherosclerotic lesions, we assessed whether eRNA generated by the macrophages themselves may induce inflammatory responses within macrophages, independent of Toll-like receptor signaling. Recombinant mouse macrophage CSF-driven bone marrow-derived macrophage (BMDM) differentiation was skewed towards the M1 phenotype by exposure of cells to eRNA. This resulted in the overexpression of inflammatory markers such as Tnf-α, Arg2, Il-1β, Il-6, or Ifn-Γ together with Il-12 and iNOS, whereas anti-inflammatory genes such as Il-10 and Il-4 together with Arg1 and macrophage mannose receptor-2 (Cd206) were significantly down-regulated by eRNA. Accordingly, the release of TNF-α and IL-6 proteins into the cell supernatant was significantly elevated by eRNA stimulation. Moreover, the capacity of granulocyte macrophage CSF-driven BMDM differentiation (already representing M1 phenotype) towards further M1 polarization in response to eRNA was moderate. Nevertheless, a significant down-regulation of M2 markers was found. Sialoadhesin-1 (SN-1) is a membrane-anchored basic protein, predominantly expressed on macrophages and involved in cellular interactions via recognition of sialylated glycoconjugates. Interestingly, exposure of SN-1-/- BMDM towards eRNA resulted in prominent down-regulation of pro-inflammatory cytokines together with M1 phenotype markers, while anti-inflammatory cytokines together with M2 phenotype mediators were significantly raised. In accordance with our proposal that eRNA serves as pro-inflammatory "alarm signal" during physiologically distressed conditions, these data may shed light on the role of eRNA and macrophages in chronic inflammatory environment such as atherosclerosis. The self-perpetuating process of atherosclerosis as a largely inflammation-driven pathology may be controlled by SN-1 expression on lesional macrophages as well as the injury-mediated release of eRNA as a master trigger in inflammation.